IMPLEMENTASI TRADISI PONDOK PESANTREN DALAM MEMBENTUK KARAKTER SISWA DI MIS NU AL-UTSMANI PEKALONGAN - Musa, Muhammad Maskur; Rahman, Muhammad Minanur; Nasarruddin, Razie Bin (Jurnal Suluh Pendidikan, 2022)
attitudes, feelings, words, and actions based on the principles of religion, law, manners, culture, and customs. Character must be owned by every human being, because character is an identity within a person and a differentiator from one person to another. Apart from being an identity, the character in a person is used as a guide in living life. The purpose of this study is to explain the implementation of the tradition of Islamic boarding schools in shaping the character of students at MIS NU Al-Utsmani Pekalongan. This research method uses descriptive qualitative, data collection through observation, interviews and documentation. The results of the study explain that the traditional values ​​of Islamic boarding schools in shaping character, these traditions are reflected through the learning carried out. MIS NU Al-Utsmani in his learning took several subjects in Islamic boarding schools such as the science of recitation, the book of Alala, and the book of Taklim Muta'alim. In addition, it is also reflected in activities such as praying, reading Asmaul Husna, praying Duha in congregation, and shaking hands with teachers. And the distinctive voices that exist in the Islamic boarding school every day continue to echo such as reading nadhoman alala books, tasrifan, imriti and Jurumiyah. The traditional values ​​of the Islamic boarding school can shape characters such as cognitive in students, discipline and most importantly religious character.